Development of a CYP11B2 imaging tracer for primary aldosteronism: basic evaluation of iodine- and fluorine-incorporated pyridinyldihydroquinolinone derivatives - Yusuke Yagi; Hiroyuki Kimura; Riko Fuseda; Takaaki Murakami; Marina Omokawa; Kaito Ohta; Satoko Kise; Masakatsu Sone; Hiroyuki Yasui; Nobuya Inagaki; Hideo Saji (EJNMMI Radiopharmacy and Chemistry)
Abstract Background Current methods for diagnosing primary aldosteronism (PA) are limited by their invasiveness and diagnostic accuracy. This study aimed to develop nuclear medicine imaging tracers targeting CYP11B2, which is overexpressed in patients with PA. Results We successfully synthesized iodinated and fluoroethoxynated pyridinyldihydroquinolinone (PDHQ) derivatives, among which PDHQ-1 exhibited the highest selectivity for CYP11B2. Furthermore, [125I]PDHQ-1 accumulated in the adrenal gland soon after administration, reaching its highest saturation compared to that in other organs 5 min after administration; however, its radioactivity decreased over time. Autoradiographic analysis revealed that [125I]PDHQ-1 displayed a 4.4-fold higher accumulation in the CYP11B2 region of adrenal sections from human patients with aldosterone-producing adenomas than in the CYP11B1 region. In contrast, [125I]IMTO, which is a highly specific radiotracer for imaging adrenocortical tissue, displayed similar accumulation in the CYP11B2 and CYP11B1 regions. Conclusions Collectively, our results suggest that [125I]PDHQ-1, featuring a pyridinyldihydroquinolinone scaffold, shows potential as an imaging tracer for PA.